2020
DOI: 10.1515/ohs-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and annual variability in chlorophyll-a in the shelf region of the Northern Bay of Bengal using MODIS-Aqua data

Abstract: Chlorophyll-a (Chl-a) concentration is an important issue in ocean ecosystem management and research. This study investigates seasonal and annual variability in Chl-a and its relationship with sea surface temperature (SST) and river discharge in the shelf region of the Northern Bay of Bengal (BoB), as well as validates satellite data against in-situ data. Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua satellite data on Chl-a concentration and SST from 2002–2018 were used in this study. River discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Plenty of nutrients are deposited along with the sediments to the Bangladesh coast in the northern BoB from the confluence of two major river systems: the Ganges and the Brahmaputra system and the whole Ganga-Brahmaputra-Meghna [23,37,41] during the southwest monsoon [38]. However, a recent study [17] for the years 2012-2017 at the shelf region in the northern BoB found a decreasing trend of Chl-a during the premonsoon due to the lower wind speed and rise in temperature. The same trend was observed for the year 1999-2000 by Nagamani et al [24].…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Plenty of nutrients are deposited along with the sediments to the Bangladesh coast in the northern BoB from the confluence of two major river systems: the Ganges and the Brahmaputra system and the whole Ganga-Brahmaputra-Meghna [23,37,41] during the southwest monsoon [38]. However, a recent study [17] for the years 2012-2017 at the shelf region in the northern BoB found a decreasing trend of Chl-a during the premonsoon due to the lower wind speed and rise in temperature. The same trend was observed for the year 1999-2000 by Nagamani et al [24].…”
Section: Resultsmentioning
confidence: 98%
“…During the summer monsoon (June-September), increased wind-driven upwelling along the eastern coast of India brings nutrient-rich waters to the surface, leading to increased Chl-a concentrations in the northern BoB region [1,14,16,23]. The season (Jul-Sep) has higher river discharge [17] enriched with higher amounts of nutrients like nitrate, silicon, and phosphate [34] due to river runoff following monsoonal rainfall [1] that causes a substantial increase of Chl-a abundance during this season. [23,37,42].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations